Estudio de los diferentes procesos de elaboración, estabilidad y almacenamiento de tres tipos de Bebidas fermentadas de Yuca (manihot esculenta crantz), con Kéfir y Levadura. - Díaz Simbaña, Paul Alexis (2020)
This research project was carried out with the purpose of establish and standardize procedures for the elaboration, storage and stability of three types of Cassava fermented beverages (Manihot esculenta), with kefir and yeasts. To reach the main aim the following bibliographic resources were studied "EVALUATION OF THE FERMENTATION OF CASSAVA (Manihot esculenta) TESTED TO THREE PROCESSES WITH KÉFIR AND YEAST FOR THE OBTAINING OF FERMENTED BEVERAGES", by Mena Alvarez Mayuri Yajaira, Santamaria Flores Jhony Alexander, STABILIZATION OF FOUR ANCESTRAL PACKAGED BEVERAGES FERMENTED WITH KEFÍR AND YEAST, by Pilamala Arcos Christian Jonnathan and the “STORAGE STUDY TO DETERMINE THE SHELF LIFE OF THREE ANCESTRAL FERMENTED BEVERAGES WITH LOW ALCOHOLIC CONTENT” by Arias Quispe Andrea and Quilapanta Ortiz Ana Best treatments were taken, unified and improved with flow diagrams, preparing the beverages, and controlling their shelf life for 15 days of each of the samples, controlling acidity parameters, ºBrix, pH and temperature, which were compared bibliographically with those carried out in previous researchers, basing on the pH the average starts at 5 to 5.4 in case of the three drinks and the final with an average of 4. For the ºBrix it was observed that they increased with respect to the long shelf life of the product began with 5 ° Brix and ended with an average of 10 to 12 ºBrix, for acidity in the same way, an increase in analytical change was observed during the 15 control days, starting with 0.5 ml of initial change and finished with a modification of 15 to 16 ml of final turn. This research is also based on the elaboration of three rheological procedures. Which will be standardized in future researches for the observation and behavior of this type of fluids, giving a plus to the instrumental and physical-chemical research of the Ancestral Beverages project of the Universidad Técnica de Cotopaxi.